Collecting sociodemographic data in primary care: qualitative interviews in community health centres - Rachel Thelen; Sara Bhatti; Jennifer Rayner; Agnes Grudniewicz (BJGP Open)
Background: Many primary care organisations do not routinely collect sociodemographic data (SDD), such as race, sex, or income, despite the importance of these data in addressing health disparities. Aim: To understand the experiences of primary care providers and staff in collecting SDD. Design & setting: A qualitative interview study with 33 primary care and interprofessional team members from eight Ontario community health centres (CHCs). Method: Semi-structured virtual interviews were conducted between July and August 2021. The interviews were recorded and transcribed verbatim. Content analysis of the transcripts was undertaken. Results: Participants reported using both formal methods of SDD collection, and informal methods of SDD collection that were more organic, varied, and conducted over time. Participants discussed sometimes feeling uncomfortable collecting SDD formally, as well as associated burden and limited resources to support collection. Client–provider rapport was noted as facilitating data collection and participants suggested more training, streamlined data collection, and better communication about purpose and use of data. Conclusion: SDD can be collected informally or formally, but there are limitations to informally collected data and barriers to the adoption of formal processes.